Evaluation of the Relationship between Cystatin C Level in Whole Saliva and Chronic Periodontitis - Mohammad Hassan Najafi Neshli; Morteza Taheri; Hooshang Rafatpanah; Amir Moeintaghavi; Majid Reza Mokhtari; Maryam Mohammadzade Rezae; Fateme Farazi
Introduction: Chronic periodontitis is an infectious disease resulting in inflammation in tooth supporting tissues, advanced attachment loss and bone loss. Destructive process is a result of imbalance between analyzing enzymes such as MMPs and their inhibitors. This imbalance can also occur with other enzymes such as lysosomal cysteine proteinase, Katpsyn and their inhibitor such as cystatin. Cystatin C is a protein which controls activity of extracellular cysteine proteinase in inflammatory conditions. The aim of this study was to evaluate the protective role of salivary cystatin C in periodental disease. Materials & Methods: Twenty six patients with chronic periodontitis examined by a periodontist and also with a minimum pocket depth of six mm and more in at least eight locations in the mouth were selected. To collect Total non-irritating saliva samples, the spit method was used. Salivary levels of cystatin C was evaluated by ELISA method. Data were analysed by SPSS version 11.5 software.Results: The level of cystatin C in periodontally diseased subjects was higher than that of the control group, but the difference was not statistically significant (P=0.24). In the female group with control of age variant, the level of cystatin C was significantly higher in patients with periodontitis (P=0.036), whereas in male group, the difference was not significant (P=0.086). It seems that the lower periodontal destruction in female group is as a result of higher level of cystatin C.Conclusion: The level of cystatin C in whole saliva could be used as a marker in chronic periodontitis.